Pain Behaviors and Physiological Parameters During Painful Procedures in Surgical Intensive Care Patients - Yeliz Sürme; Hatice Yüceler Kaçmaz; Özlem Ceyhan; İlker Yılmaz (Galenos Yayinevi, 2023)
Objective:This research was conducted to determine the pain behaviors and physiological parameters of patients connected to mechanical ventilators in the postoperative surgical intensive care unit.Materials and Methods:This study was conducted descriptively and observationally with 176 patients. The introductory information form, physiological parameters follow-up form, behavioral pain scale (BPS), and Ramsey sedation scale were used to collect data. Descriptive statistics, Two-Way variance in repeated measures, Friedman analysis, post-hoc Bonferroni analysis, One-Way variance analysis, Kruskal-Wallis analysis, and Spearman correlation analysis were used.Results:The mean arterial pressure (MAP), heart rate and mean BPS scores increased (p<0.001), and oxygen saturation decreased during aspiration, wound care, and position change (p<0.001). Additionally, while a moderate, positive correlation was found between BPS and MAP and heart rate during wound care (r=0.447; p=0.001, r=0.306; p=0.033). A moderate negative correlation was found between oxygen saturation and BPS during aspiration (r=-0.389; p=0.000).Conclusion:It has been revealed that individuals connected to mechanical ventilators experience pain during wound care, position change and aspiration. Physiological parameters and behavioral symptoms resulting from pain should be analyzed together. Pain should be relieved with pharmacological and non-pharmacological nursing interventions in pain management.